Exclusion, inclusion and belonging in mainstream and disability sport: Jack's story. Issue 1 (2nd January 2023) - Maher, Anthony John; McVeigh, Joanne; Thomson, Alan; Knight, Jack
ABSTRACT: Concepts of exclusion and inclusion in sport, physical activity and physical education settings are mostly anchored to discussions about access to and opportunities in physical and social spaces from the perspective of non-disabled adult stakeholders. In this article, we use individual interviews and two creative non-fiction accounts to explore the views of an adult with cerebral palsy (CP), named Jack, who reflects on his embodied experiences of mainstream and CP youth football. This approach enabled us to provide a more nuanced and sophisticated consideration of the exclusion/inclusion dichotomy by centring Jack's construction of identity and feelings of belonging in the spaces his body inhabited. Particular attention is paid to the interactions and relationships that Jack developed with teammates and coaches, and the (often ableist) constructs of ability that pervade mainstream and CP settings, all of which served to influence Jack's sense of belonging. We end by encouraging scholars to centre the experiences and amplify the voices of disabled young people, and to consider inclusion as intersubjective experiences associated with feelings of belonging, acceptance and value that are dynamic and in flux. The concept of embodied belonging can help us to move researchers beyond a simple critique of disabling socio-spatial power relations towards the construction of new knowledge that enhances understandings of disability, place, and space.